Changes in circulating forms of anti-Muüllerian hormone and androgens in women with and without PCOS: a systematic longitudinal study throughout pregnancy. Issue 5 (15th March 2023) - Peigné, M; Simon, V; Pigny, P; Mimouni, N E H; Martin, C; Dewailly, D; Catteau-Jonard, S; Giacobini, P
Abstract: STUDY QUESTION: What are the changes in serum concentration of total and cleaved anti-Muüllerian hormone (AMH) molecular forms and of androgens before and throughout pregnancy in women with and without polycystic ovary syndrome (PCOS) in a longitudinal follow-up investigation? SUMMARY ANSWER: Serum levels of total and cleaved AMH are higher from preconception to the third trimester of pregnancy in women with PCOS as compared to controls, whereas testosterone and androstenedione levels are higher in women with PCOS than in control women before pregnancy and during the second and third trimester of pregnancy. WHAT IS KNOWN ALREADY: Cross-sectional or partial longitudinal studies have shown higher AMH and androgen levels in pregnant women with PCOS as compared with non-PCOS women. To date, no complete longitudinal dynamic monitoring of the circulating forms of AMH and androgens from pre-conception to the third trimester of pregnancy have compared women with and without PCOS. STUDY DESIGN, SIZE, DURATION: This systematic prospective quarterly longitudinal monocentric study was a comparative follow-up of 30 women with PCOS and 29 controls before and during pregnancy from April 2019 to July 2022. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women aged 18–43 years with a pre-conception measurement of AMH were included during the first trimester of a singleton pregnancy. The PCOS group was defined according to the Rotterdam diagnostic criteria. The control group patients included in the study had normal ovarian reserves. Circulating total and cleaved AMH, and serum estradiol, LH, and androgen levels were measured during the first, second, and third trimester of pregnancy in all study participants. MAIN RESULTS AND THE ROLE OF CHANCE: Before pregnancy, patients with PCOS had higher levels of AMH than controls. The total and cleaved AMH forms were significantly higher in women with PCOS than controls from pre-conception to the third trimester of pregnancy (all P  <   0.001). Androgens (total testosterone and androstenedione) were higher in women with PCOS than controls from mid-pregnancy onwards. LIMITATIONS, REASONS FOR CAUTION: Our control population was a population of infertile women with no ovarian problems but most of them had undergone ART treatments to achieve pregnancy. WIDER IMPLICATIONS OF THE FINDINGS: These results strengthen the hypothesis that gestational hyperandrogenism as well as exposure to elevated AMH levels in utero could be driving forces predisposing female progeny to develop PCOS. STUDY FUNDING/COMPETING INTEREST(S): Funding was provided by INSERM, France (grant number U1172) and the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation program, ERC-2016-CoG to P.G. grant agreement n° 725149/REPRODAMH. The authors have nothing to declare. TRIAL REGISTRATION NUMBER: NCT03483792